THE ROLE OF LEADERSHIP STYLE AND WORK MOTIVATION ON THE EFFECTIVENESS OF THE FREE NUTRITIOUS MEAL PROGRAM WITH ORGANIZATIONAL CULTURE AS A MODERATING VARIABLE - Firdaus; Ahmad Firman; Fitriani Latief (SOSIOEDUKASI, 2026)
This study analyzes the influence of leadership style and work motivation on the effectiveness of the Free Nutritional Meal Program (MBG) with organizational culture as a moderating variable. The study used a quantitative approach with a causal design and was conducted at the Nutrition Fulfillment Service Unit (SPPG) in Makassar City. The sample size was 98 respondents determined using the Slovin formula. Data were collected through questionnaires distributed to parties directly involved in program implementation and analyzed using SEM-PLS. The results showed that leadership style and work motivation had a positive and significant effect on program effectiveness. Organizational culture was proven to strengthen this relationship. This study supports the New Public Management theory, which emphasizes the importance of strengthening managerial capacities and an adaptive organizational culture to improve public sector performance. These findings imply that the quality of leadership, work motivation, and a results-oriented organizational culture determines the effectiveness of social policy.